2015
DOI: 10.5709/acp-0169-3
|View full text |Cite
|
Sign up to set email alerts
|

Invisible Stimuli, Implicit Thresholds: Why Invisibility Judgments Cannot be Interpreted in Isolation

Abstract: Some studies of unconscious cognition rely on judgments of participants stating that they have “not seen” the critical stimulus (e.g., in a masked-priming experiment). Trials in which participants gave invisibility judgments are then treated as those where the critical stimulus was “subliminal” or “unconscious,” as opposed to trials with higher visibility ratings. Sometimes, only these trials are further analyzed, for instance, for unconscious priming effects. Here I argue that this practice requires implicit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
88
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 54 publications
(73 reference statements)
0
88
1
Order By: Relevance
“…While the validity of subjective reports is subject to some controversy (Schmidt, ), a recent integrative research article that accepts the subjective report criterion has summarized the available data concluding that “discrimination performance is typically better on seen than on unseen trials, even when the physical stimuli are physically identical” (King & Dehaene, , p. 2, italics added). As the authors further state.
…although objective discrimination can be above chance with subjectively invisible stimuli, such unconscious discrimination performance is at best mediocre.
…”
Section: Tipping the Balance For Overflowmentioning
confidence: 99%
“…While the validity of subjective reports is subject to some controversy (Schmidt, ), a recent integrative research article that accepts the subjective report criterion has summarized the available data concluding that “discrimination performance is typically better on seen than on unseen trials, even when the physical stimuli are physically identical” (King & Dehaene, , p. 2, italics added). As the authors further state.
…although objective discrimination can be above chance with subjectively invisible stimuli, such unconscious discrimination performance is at best mediocre.
…”
Section: Tipping the Balance For Overflowmentioning
confidence: 99%
“…Although introspective judgments of perception have face validity (Cleeremans, 2011), it is also clear that a self-reported lack of perception may not indicate an actual lack of perception but rather a lack of confidence (Holender, 1986; Björkman et al, 1993; Wiens, 2007). This may be especially problematic when self-reports are used in isolation to divide trials into conscious and unconscious bins (Schmidt, 2015). In the absence of a consensus on how to measure perception, it is therefore important to compare effects based on both types of measures.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have pointed out the limitations of using accuracy and confidence measures to assess perceptual awareness, and suggested remedies including the calculation of metacognitive sensitivity measures (25), Bayesian statistics (26), or parametric variation of the experimental manipulation (27). The present study addresses an issue not covered in previous discussions, by showing Notably, a previous study (10) that used CFS to investigate acquisition of threat responses without awareness of the stimuli found that such acquisition can occur, but is rapidly forgotten.…”
Section: Discussionmentioning
confidence: 99%